Injectable polyethylene glycol-laponite composite hydrogels as articular cartilage scaffolds with superior mechanical and rheological properties. Issue 3 (11th February 2017) - Nojoomi, Amirali; Tamjid, Elnaz; Simchi, Abdolreza; Bonakdar, Shahin; Stroeve, Pieter
ABSTRACT: In this study, injectable PEG-based hydrogels containing Laponite particles with mechanical and structural properties close to the natural articular cartilage are introduced. The nanocomposites are fabricated by imide ring opening reactions utilizing synthesized copolymers containing PEG blocks and nanoclay through a two-step thermal poly-(amic acid) process. Butane diamine is used as nucleophilic reagent and hydrogels with interconnected pores with sizes in the range of 100–250 µm are prepared. Improved viscoelastic properties compared with the conventional PEG hydrogels are shown. Evaluation of cell viability utilizing human mesenchymal stem cells determines cytocompatibility of the nanocomposite hydrogels. GRAPHICAL ABSTRACT: